Large-scale numerical modeling of hydro-acoustic waves generated by tsunamigenic earthquakes - C. Cecioni; A. Abdolali; G. Bellotti; P. Sammarco (Natural Hazards and Earth System Sciences, 2015)
Tsunamigenic fast movements of the seabed generate pressure waves in weakly compressible seawater, namely hydro-acoustic waves, which travel at the sound celerity in water (about 1500 m s−1). These waves travel much faster than the counterpart long free-surface gravity waves and contain significant information on the source. Measurement of hydro-acoustic waves can therefore anticipate the tsunami arrival and significantly improve the capability of tsunami early warning systems. In this paper a novel numerical model for reproduction of hydro-acoustic waves is applied to analyze the generation and propagation in real bathymetry of these pressure perturbations for two historical catastrophic earthquake scenarios in Mediterranean Sea. The model is based on the solution of a depth-integrated equation, and therefore results are computationally efficient in reconstructing the hydro-acoustic waves propagation scenarios.